One-Pot Synthesis of 1,8-Dioxo-octahydroxanthenes Utilizing Silica-Supported Preyssler Nano Particles as Novel and Efficient Reusable Heterogeneous Acidic Catalyst - Ali Javid; Majid M. Heravi; Fatemeh F. Bamoharram (E-Journal of Chemistry)
A highly efficient one-pot synthesis of 1,8-dioxo-octahydroxanthenes from dimedone and various aromatic aldehydes under reflux conditions in water, catalyzed by silica-supported preyssler nano particles (SPNP) is reported. The products were formed in excellent yields and the acidic catalyst was completely heterogeneous and can be recycled for many times.